Web filtering : Experimentation at FTMSK / Norhamidah Hj Sarkam - Hj Sarkam, Norhamidah (2004)
This project deals with the subject of Web filtering. Specifically, the place of interest is the Faculty of Information Technology and Quantitative Sciences (FTMSK) at MARA University of Technology in Shah Alam. Web filtering will concern the students, staff and lectures, and whoever is using the web services at FTMSK. This project aims to propose solution for inappropriate and malicious web contents. Control of these contents will be achieved through filtering methodology. The proposed solution will be implemented and tested at FTMSK. The web filtering solution will empower administrator to effectively manage the web usage by limiting end-users access to certain sites and curbing the network from viruses and worms. Consequently, this project can help to avoid bandwidth loss due to congestion and maintain network performance from deterioration.